Eksplorasi Antioksidan dan Anti-Inflamasi Madu Hutan Pulau Buton Secara in-Vitro dan Efek Inhibisi Edema Telinga Secara in-Vivo - Hariana; Wahyuni; Loly Subhiaty Idrus; Fadhliyah Malik; La Ode Muhammad Julian Purnama; Adryan Fristiohady (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
Forest honey is a natural product derived from the nectar of wild plants and is known to contain various bioactive compounds, such as flavonoids and phenolics, which contribute to its antioxidant and anti-inflammatory potential. Buton Regency in Southeast Sulawesi is recognized as a producer of forest honey; however, scientific studies on its biological activities remain limited. This study aimed to evaluate the free radical scavenging activity and anti-inflammatory effects of Buton forest honey through both in vitro and in vivo approaches. Antioxidant activity was assessed using DPPH and ABTS assays, while anti-inflammatory evaluation involved inhibition of BSA protein denaturation and a mouse ear edema model induced by xylene. The honey exhibited IC₅₀ values of 71.69 ± 2.73 mg/L (DPPH) and 49.23 ± 4.24 mg/L (ABTS). Its protein denaturation inhibition showed an IC₅₀ of 14.17 ± 3.18 mg/L. In vivo testing demonstrated that high-dose honey significantly reduced ear thickness in mice, with a percentage of inhibition comparable to diclofenac sodium. Statistical analysis revealed significant differences (p < 0.05) across most parameters. These findings indicate that Buton forest honey holds promise as a natural antioxidant and anti-inflammatory agent.